Ovulation Latency: A Case Study of Koi Fish (Cyprinus rubrofuscus) Spawning using Gonadotropin Hormones with Different Doses - Akbarurrasyid, Muhammad; Mahardika, Muhamad Fazli; Zainul Arifin, Irvan Firman Syah; Sudinno, Dinno (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
Spawning of koi fish (Cyprinus rubrofuscus) using gonadotropin hormone is a step in providing fish seeds. This study aims to determine the ovulation latency of C. rubrofuscus fish spawned using gonadotropin hormone with different doses on the resulting fecundity, fertilization rate, hatching rate and survival rate produced. The study was conducted using an ex post causal design method at a koi fish hatchery unit in the Sukabumi area. The experimental results were analyzed using ANOVA statistics to compare between treatments. The fastest ovulation latency and highest fecundity values ​​were obtained at a dose of 0.5 ml/kg (sex ratio 1:1) which was 8.25 hours with a fecundity value of 120,000 eggs. While the highest FR value was obtained at a dose of 0.3 ml/kg (sex ratio 1:2) of 88%. The best HR value was obtained at a dose of 0.2 ml/kg (sex ratio 1:3) which was 80% with an SR value of 72%. The ovulation latency value was faster at a high dose so that it affected the fecundity value (p<0.05). However, the high fecundity number did not all represent the quality of the eggs produced, this can be seen in the lower FR value compared to the dose of 0.3 ml/kg (sex ratio 1:2). The results of the study showed that the FR and HR values ​​were different due to different dose and sex ratio factors. The difference in sex ratio affects the hatching process which is caused by the uneven fertilization time of koi fish. In general, fecundity, fertilization rate, and hatching rate significantly influenced ovulation latency (p<0.05). The results of this study are expected to provide information regarding the use of gonadotropin doses in the spawning process, especially regarding ovulation latency and other spawning parameters.